2020
DOI: 10.1101/2020.08.07.20170258
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Salivary anti-SARS-CoV-2 IgA as an accessible biomarker of mucosal immunity against COVID-19

Abstract: Background: Mucosal immunity, including secretory IgA (sIgA), plays an important role in early defenses against respiratory pathogens. Salivary testing, the most convenient way to measure sIgA, has been used to characterize mucosal immune responses to many viral infections including SARS, MERS, influenza, HIV, and RSV. However, its role has not yet been characterized in the COVID-19 pandemic. Here, we report development and validation of a rapid immunoassay for measuring salivary IgA against the SARS-CoV-2 v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 65 publications
(78 reference statements)
1
76
0
1
Order By: Relevance
“…Indeed, although Randad et al 14 showed good specificity for IgA, sensitivity did not exceed 61%. However, more recent work by Varadhachary et al 22 reports a rapid immunoassay designed for point-of-care use that showed 92% positive agreement and 97% negative agreement in 36 and 32 samples respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, although Randad et al 14 showed good specificity for IgA, sensitivity did not exceed 61%. However, more recent work by Varadhachary et al 22 reports a rapid immunoassay designed for point-of-care use that showed 92% positive agreement and 97% negative agreement in 36 and 32 samples respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Although abundant literature exists on systemic immune responses to natural SARS-CoV-2 infection, literature on mucosal immunity is currently limited. In mucosal fluids 297 from COVID-19 patients, S and RBD-specific IgA, IgG, and IgM were readily detected [24][25][26] . It is 298 hypothesized that sIgA mainly protects the upper respiratory tract, whereas systemic IgG 299 protects the lower respiratory tract 14,27,28 .…”
Section: Figure 1 Sars-cov-2 Challenge Of Syrian Hamsters Vaccinatedmentioning
confidence: 97%
“…Antibody titres can decrease 7 d after infection 56 . Recent studies have identified SARS-CoV-2-specific antibodies in the saliva 59,60 . Multiplex SARS-CoV-2 antibody immunoassays were investigated to determine differences between antibody levels in saliva and sera.…”
Section: Detection Of Sars-cov-2 Antibodiesmentioning
confidence: 99%